Roma as actors in negotiating housing policies during state socialism. The case study of Podunajské Biskupice and Plavecký Štvrtok (1950–1989) - Stachová, Monika (Romano džaniben, 2024)
The text examines the negotiation of local housing politics in Slovakia between the 1950s and 1980s and the agency of local Roma in this process, focusing on the diversity of their political strategies, their positioning, influence and limits of their political participation. The research is based on data from two municipalities in western Slovakia. In one of them, the Romani actors were fighting against existing discriminatory strategies and other factors posing limits to their participation. The other municipality was honored as a model of interethnic cooperation for the rest of Slovakia. Nevertheless, during the late 1970s, the situation has rapidly changed also in this locality. The text inserts the two specific experiences within the broader historical, social, and political context. The author attempts to analyze the dynamics of the changes in the local policies and the determinants that played a crucial role in the success or failure of the demands by the Roma. While doing so, the author focuses on two levels of political participation – on the one hand in the framework of the Slovak Union of Gypsies Roma, and on the other hand, within the local administrative structures.